2011
DOI: 10.1089/jmf.2010.0005
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Soymilk Lowers Atherogenic Lipid Fraction in Healthy Individuals

Abstract: The effect of soy-based products on lipid profile has not been well established. Whereas some investigators have reported that soy is hypocholesterolemic, others could only demonstrate this in hypercholesterolemic subjects, while a few have not found any marked association between soy and cholesterol levels. This study was therefore aimed at investigating the effect of soymilk on lipid and lipoprotein profile of normocholesterolemic, apparently healthy Nigerian Africans. Five hundred milliliters of soymilk pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The subjects in present study were young and healthy women without any chronic disease. Most study in field of soy and CVDs are conducted mainly in postmenopausal women or hypercholestrolemic or diabetic subjects [ 7 12 22 ]. Previous studies revealed that favorable effects of soy product on lipid profile are more noticeable in individuals with hypercholesterolemia [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects in present study were young and healthy women without any chronic disease. Most study in field of soy and CVDs are conducted mainly in postmenopausal women or hypercholestrolemic or diabetic subjects [ 7 12 22 ]. Previous studies revealed that favorable effects of soy product on lipid profile are more noticeable in individuals with hypercholesterolemia [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were; use of drugs known to interference with the study protocol, incidence of any chronic or acute disease after starting the project, smoking and adherence to a specific regimen. The formula for cross-over trials [ 21 ], n = [(Z 1-α/2 + Z 1-β ) 2 × S 2 ] / 2(Δ) 2 , and LDL cholesterol (LDL-C) as the principle variable [ 22 ], were used for calculating the study sample size; where S was the variance of LDL-C and Δ was the differences in mean of LDL-C. Given the Z 1-α/2 = 1.96, Z 1-β = 0.85, S = 1 and Δ = 0.4, the sample size needed for the study was 24 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…They further concluded from their study that soy remains one of a few food components that reduces serum cholesterol (>4%) when added to the diet. In a more recent study, Onuegbu et al (2011) fed 500 mL of soymilk daily to 42 apparently healthy young to middle-aged subjects for a period of 21 days and reported that soymilk consumption significantly reduced mean plasma TC by 11% and LDL-C by 25% and increased mean plasma HDL-C by 20%. The authors also concluded that soy drink could be an important non-pharmacological cholesterol-reducing agent.…”
Section: Soybeans and Healthmentioning
confidence: 99%
“…Soy products including soymilk exert preferable effects on reducing the risks of cardiovascular diseases and osteoporosis, cholesterol levels, and UV radiation-induced skin inflammation [ 14 , 15 , 16 , 17 , 18 , 19 ]. Soymilk contains enriched plant proteins, essential amino acids, polyunsaturated fatty acids, vitamins and minerals.…”
Section: Introductionmentioning
confidence: 99%